A Cross-cultural, Trans-generational Portrait of Italian-Canadians in Adriana Monti’s Two Short Films - Foschi Ciampolini, Anna (Italian Canadiana, 2020)
Adriana Monti is an Italian-Canadian independent producer, feminist filmmaker and author. She started her career in Italy in the late 1970s by developing a collaborative and experimental style that allowed the women object of her research to take an active and creative role in her films. This interview centers around her two recent documentaries. Family 001 and Family 005 are two shorts exploring the lives of several influential Torontonians and Montrealers of Italian origin through a series of informal interviews with women, men and members of the same family from diverse age groups. This brings a captivating and often touching perspective of the Italian-Canadian immigrant experience. In the course of this interview, Monti explores the deeper issues of identity, integration, acculturation, shifting gender roles, generational lifestyles and career choices. She also talks about the influence/interference of government in people’s lives and in respect to creativity and cultural life.